Optimization of SARS-CoV-2 Spike Protein Expression in the Silkworm and Induction of Efficient Protective Immunity by Inoculation With Alum Adjuvants - Masuda, Akitsu; Lee, Jae Man; Miyata, Takeshi; Mon, Hiroaki; Sato, Keita; Oyama, Kosuke; Sakurai, Yasuteru; Yasuda, Jiro; Takahashi, Daisuke; Ueda, Tadashi; Kato, Yuri; Nishida, Motohiro; et al. (Frontiers in Immunology, 2022)
The newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is causing a spread of coronavirus disease 2019 (COVID-19) globally. In order to end the COVID-19 pandemic, an effective vaccine against SARS-CoV-2 must be produced at low cost and disseminated worldwide. The spike (S) protein of coronaviruses plays a pivotal role in the infection to host cells. Therefore, targeting the S protein is one of the most rational approaches in developing vaccines and therapeutic agents. In this study, we optimized the expression of secreted trimerized S protein of SARS-CoV-2 using a silkworm-baculovirus expression vector system and evaluated its immunogenicity in mice. The results showed that the S protein forming the trimeric structure was the most stable when the chicken cartilage matrix protein was used as the trimeric motif and could be purified in large amounts from the serum of silkworm larvae. The purified S protein efficiently induced antigen-specific antibodies in mouse serum without adjuvant, but its ability to induce neutralizing antibodies was low. After examining several adjuvants, the use of Alum adjuvant was the most effective in inducing strong neutralizing antibody induction. We also examined the adjuvant effect of paramylon from Euglena gracilis when administered with the S protein. Our results highlight the effectiveness and suitable construct design of the S protein produced in silkworms for the subunit vaccine development against SARS-CoV-2.